Pelatihan Kecerdasan Buatan Bagi Guru-guru Sekolah Menengah Kejuruan di Surabaya - Puspasari, Durinta; Puspasari, Durinda; Wulandari, Ruri Nurul Aeni; Panduwinata, Lifa Farida (Universitas Negeri Surabaya, 2026)
The rapid advancement of technology, particularly in the field of artificial intelligence (AI), has had a positive impact on enhancing learning effectiveness. However, this progress also poses a challenge for the education sector to better understand the role and contribution of AI in achieving educational objectives and fostering scientific development. Training programs on artificial intelligence for teachers serve as an effective means to strengthen their competencies in integrating AI applications into classroom instruction. Through such training, teachers are expected to enhance students’ learning motivation and engagement. This community service activity was conducted at IPIEMS Vocational High School Surabaya and involved 33 participants consisting of Vocational High School teachers from the Office Management Automation Study Program and lecturers from the Undergraduate Office Administration Education Study Program, Universitas Negeri Surabaya. The training was implemented through a combination of lectures and hands-on practice sessions using AI tools. The results showed a highly positive response from the participants. Regarding the relevance of training materials to participants’ needs, 51.5% rated it as very good; for material comprehensibility and applicability, 45.5% rated it as very good; for the clarity and systematic delivery of materials, 69.7% rated it as very good; for the presenters’ mastery of the material, 72.7% rated it as very good; and for the clarity and satisfaction of answers during the discussion sessions, 51.5% rated it as very good. The participants demonstrated high enthusiasm throughout the training and expressed their interest in participating in similar programs in the future to continuously support the sustainable integration of artificial intelligence in education